Home Lighting Installation Using Smart Home System - Mappadang, Jusuf Luther; Nongka, Gloria Christania; Lumairo, Febrian; Lumi, Christian; Kapoh, Ariel (Cerdika: Jurnal Ilmiah Indonesia, 2025)
The smart home system is a modern technology that provides convenience in the processing of home lighting automatically and integrated. This study aims to design and implement a smart home-based lighting system to improve energy efficiency and user comfort.The method used is to whiten the installation of smart lights and smart switches that are connected to the controller application.test results show that the system is able to reduce energy consumption by up to 30% through automation and remote control. The methods used in this study include the analysis of energy lighting needs, the installation of smart lights and automatic switches connected to the internet network, as well as the integration of the system with internet-based control applications off things (lot). Trials were conducted to observe the effectiveness of the system in saving energy and improving user comfort. The test results show that the smart lighting system developed is able to reduce energy consumption by up to 30% compared to conventional lighting systems. In addition, the system allows real-time lighting control remotely via mobile devices, providing flexibility and convenience in household energy management. These findings support the use of smart home systems as an innovative solution to create more energy-efficient and environmentally friendly homes.